2018
DOI: 10.1083/jcb.201802117
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and epitranscriptomics in temporal patterning of cortical neural progenitor competence

Abstract: Yoon et al. review epigenetic and epitranscriptomic mechanisms that regulate the lineage specification of neural progenitor cells in the developing brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 177 publications
4
76
0
Order By: Relevance
“…Transmission of temporal birthmarks from mother to daughter cell may occur via conserved local-or large-scale chromatin features, as suggested by the critical role of epigenetic regulation in temporal patterning identified here. In addition, the passive transmission of cytoplasmic RNA and posttranscriptional events may also be involved (17,(45)(46)(47)(48). This temporal birthmark fades with differentiation as environmental factors come into play.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of temporal birthmarks from mother to daughter cell may occur via conserved local-or large-scale chromatin features, as suggested by the critical role of epigenetic regulation in temporal patterning identified here. In addition, the passive transmission of cytoplasmic RNA and posttranscriptional events may also be involved (17,(45)(46)(47)(48). This temporal birthmark fades with differentiation as environmental factors come into play.…”
Section: Discussionmentioning
confidence: 99%
“…including an increase in repressive histone marks, a local change in nucleosome occupancy, or a general increase in histones' levels (Fiszbein et al, 2016;Gavin et al, 2017;Yoon et al, 2018). It was reported that the nuclei of ESCs macroscopically appear to contain less condensed chromatin, whereas well-defined foci of compact heterochromatin become evident in ESC-derived NPCs (Meshorer et al, 2006).…”
Section: Kinetic Coupling Is Enhanced In Neuronsmentioning
confidence: 99%
“…17 . These epigenetic modifications are believed to be important to specify the lineage fidelity of different cell types during neurogenesis 15,[18][19][20][21] . For example, H3K27me3 is widely associated with important lineage genes and maintain them at a repressed but poised state in stem cells, as demonstrated by genome-wide mapping studies [22][23][24][25] .…”
mentioning
confidence: 99%